Peranan institusi sains dan penyelidikan dalam pembangunan sosioekonomi Negeri-Negeri Melayu Bersekutu, 1896-1941 / Sawi Linus Sungat - Sawi Linus, Sungat (2017)
This study aims to examine the roles of science and research institutions in the socioeconomic development of the Federated Malay States (FMS) from 1896 to 1941. Of main consideration is the role played by British administrators in establishing scientific institutions in schools and higher education institutions, economic research institutes (Research Institute of Forest and Rubber Research Institute) and social research institute (Institute for Medical research). The study has proven that the decision made by the British administrators to establish the four scientific institutions had successfully met the requirements of technical manpower particularly in the industrializing economy of the Federated Malay States. The economic institutions on the other hand were able to develop forest resources and increase forest products to generate economic growth, and seek new techniques in planting rubber. The social research institute manages to find remedial measures for deadly and infectious diseases that were prevalent among immigrant labourers; thus, promoting the production of cash crops and minerals such as rubber and tin. Therefore, it has been proven that the four institutions were the essential heartbeat of the socio-economic development of the Federated Malay States.